2010
DOI: 10.1007/s11999-009-0873-z
|View full text |Cite
|
Sign up to set email alerts
|

Do Intraoperative Radiographs in Scoliosis Surgery Reflect Radiographic Result?

Abstract: It is often difficult to predict postoperative radiographic curve magnitude and balance parameters while performing intraoperative correction during scoliosis surgery. We asked whether there was a radiographic correlation between intraoperative long-cassette scoliosis film and postoperative standing radiographs of adolescent idiopathic scoliosis with pedicle screw instrumentation. We retrospectively reviewed 44 patients with adolescent idiopathic scoliosis who underwent posterior instrumentation with pedicle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…Similar to previous researchers [12] we found a strong correlation for proximal thoracic, main thoracic, and thoracolumbar/lumbar curves (r = 0.73, 0.83, and 0.84, respectively; P < 0.05) between the IO and IPO radiographs. The strong correlation persisted when the IO radiographs were compared with the standing radiographs done several months later (r = 0.77, 0.72, and 0.88, respectively; P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to previous researchers [12] we found a strong correlation for proximal thoracic, main thoracic, and thoracolumbar/lumbar curves (r = 0.73, 0.83, and 0.84, respectively; P < 0.05) between the IO and IPO radiographs. The strong correlation persisted when the IO radiographs were compared with the standing radiographs done several months later (r = 0.77, 0.72, and 0.88, respectively; P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Lehman et al [12] reported on 44 patients with AIS from two different centers who underwent posterior spinal fusion with pedicle screw instrumentation and compared coronal plane alignment based on IO-prone radiograph with those measured on a standing full-length radiograph done in the early postoperative period. Their overall findings were quite similar to ours, as they suggested that IO radiography is a valuable tool that foreshadows the coronal plane correction noted on standing radiographs performed in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a more heterogeneous cohort, Fuzzy clustering offers solution by assigning membership grades and further developing a probabilistic path for determining the outcome groups 57 . Despite the significant relationship between the intraoperative radiographs and the surgical outcome of AIS spinal fusion 58 , a study that associates the imparted intraoperative changes in the spine and the early post-operative alignment in a larger database can better guide surgical decision making.…”
Section: Discussionmentioning
confidence: 99%